Training in Making Interactive Learning Media Using the Canva Application for Elementary School Teachers in Palembang City - Dwi Cahaya Nurani; Sardianto Markos Siahaan; Evelina Astra v; Anugrah Agung; Muhammad Asyrof; Yohana Trio Minar; Shilvi Anggraeni; Wawan Ahmad Komarudin (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This program aims to improve the ability of elementary school teachers in Palembang City to create interactive and interesting learning media for students using the Canva application. The method used in this community service activity is using training, assignments, and mentoring. The results of the training and mentoring show that elementary school teachers in Palembang City are able to produce learning media in the form of PowerPoint and interesting learning videos using the Canva application.